IMPROVING THE STUDENTS’ SPEAKING SKILL THROUGH DEBATE TECHNIQUE - Fernandes Arung; J. Jumardin (Universitas Sembilanbelas November Kolaka, 2016)
This study is based on the important of speaking skill. Speaking was important to be learnt because speaking is the way to communicate with other people in order to deliver opinion and express idea, but in fact, the students’ ability in speaking English is low. It is caused by several factors such as the elements of speaking like vocabulary, pronunciation, grammar, and fluency that must be mastered by students in order to be good English speaker. In this research, the researcher used debate technique to improve students’ speaking skill. The main objective of this study is to describe the implementation of debate technique in teaching speaking and to identify how much students’ speaking skill improvement after being taught by using debate technique. This study is classroom action research that was done in two cycles. The data collection was done using test and observation. The data from the test and observation that had been taken from every cycle were analyzed quantitatively. The implementation of debate technique in teaching speaking at the second year of SMA Negeri 1 Lasusua was conducted in two cycles including cycle one and cycle two. The participants of this study were 29 students in class XI/IPA 2. The result of this study showed that using debate technique can improve students’ speaking skill. This is proven by students’ test score that improved in every cycle. In the first cycle, the students’ average score was 64 and in the second cycle students got 78, Debate is an appropriate technique used to improve students’ speaking skill for the students at class XI/IPA 2. The result of this study is helpful information especially for the English teacher who is teaching at that class and all English teachers generally.